Genetic Determined Iron Starvation Signature in Friedreich's Ataxia - Grander, Manuel; Haschka, David; Indelicato, Elisabetta; Kremser, Christian; Amprosi, Matthias; Nachbauer, Wolfgang; Henninger, Benjamin; Stefani, Ambra; Högl, Birgit; Fischer, Christine; Seifert, Markus; Kiechl, Stefan; et al. (Movement disorders, 2024)
Background Early studies in cellular models suggested an iron accumulation in Friedreich's ataxia (FA), yet findings from patients are lacking. Objectives The objective is to characterize systemic iron metabolism, body iron storages, and intracellular iron regulation in FA patients. Methods In FA patients and matched healthy controls, we assessed serum iron parameters, regulatory hormones as well as the expression of regulatory proteins and iron distribution in peripheral blood mononuclear cells (PBMCs). We applied magnetic resonance imaging with R2*‐relaxometry to quantify iron storages in the liver, spleen, and pancreas. Across all evaluations, we assessed the influence of the genetic severity as expressed by the length of the shorter GAA‐expansion (GAA1). Results We recruited 40 FA patients (19 women). Compared to controls, FA patients displayed lower serum iron and transferrin saturation. Serum ferritin, hepcidin, mean corpuscular hemoglobin and mean corpuscular volume in FA inversely correlated with the GAA1‐repeat length, indicating iron deficiency and restricted availability for erythropoiesis with increasing genetic severity. R2*‐relaxometry revealed a reduction of splenic and hepatic iron stores in FA. Liver and spleen R2* values inversely correlated with the GAA1‐repeat length. FA PBMCs displayed downregulation of ferritin and upregulation of transferrin receptor and divalent metal transporter‐1 mRNA, particularly in patients with >500 GAA1‐repeats. In FA PBMCs, intracellular iron was not increased, but shifted toward mitochondria. Conclusions We provide evidence for a previously unrecognized iron starvation signature at systemic and cellular levels in FA patients, which is related to the underlying genetic severity. These findings challenge the use of systemic iron lowering therapies in FA. © 2024 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.